Práticas de tortura narradas em Torquemada (1971), de Augusto Boal - Fiuza, Sandra Alves (2005)
The purpose of this study was understanding and historicizing the theatrical text Torquemada (1971), by the way of the investigation of representations built about torture during the brazilian dictatorship s period by the dramatist Augusto Boal and also through the connections of the dramatic form on which the play is settled the curinga system with the social experience. We found out that in the preparation of characters acting there was an intention of the author to provoke a determinate effect in the reader/spectator, that s ever oscillating and non-excluding: sometimes using resources to suscitate the identification with the victims of torture, sometimes promoting the right critical distance to stir up repugnance against the violence shown in almost all the scenes. However, for the understanding of the narrative s organization with variable ways of implication of the reader/spectator in regard to the scene (identification or distance) was needful to reflect, previously, about the dramatist s creative process, searching the references and the repertory utilized by him. We detached the questions relative to the Teatro de Arena s public, on which we took as reference the testimonies of the group s members and also the interpretations of critics and academics studies after accomplished, as well as the stanislaviskian and brechtian references on the Boal s artistical activity. After that, we d focus the discussion about the elaboration and reproduction of a specific theatrical language the curinga system by means of the theoretical texts written by Augusto Boal and the interpretations elaborated by critics and academicians. At last, we sought to interpret the dramatic text Torquemada, taking into consideration that form doesn t exist in itself, but that the curinga system s structure just make sense when it s associated with a transmited content.